2001
DOI: 10.3346/jkms.2001.16.6.719
|View full text |Cite
|
Sign up to set email alerts
|

The Haplotype Analyses Using Multiple Markers of the Apolipoprotein B Gene in Patients with Coronary Artery Disease

Abstract: The high level of low density lipoprotein (LDL) is a risk factor for cardiovascular disease. Apolipoprotein (apo) B is a major protein component of LDL and plays an important role in the maintenance of cholesterol homeostasis. In this study, six polymorphic sites of the apoB gene were anlaysed in 235 patients with coronary artery disease (CAD) and 216 normal control subjects. There were no significant differences in the allele frequencies of apoB polymorphisms between the control and patient groups. However, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Combined genotypes or haplotypes for APOB polymorphisms consisting of some sites of the gene region have been described frequently in various ethnic populations (Renges et al 1992;De Benedictis et al 1993;Wu et al 1993;Hansen et al 1994;Hallman et al 1994;Anderson et al 1997;Hong et al 2001;Puri et al 2003). In comparison with the combined genotypes of four sites (AluI, XbaI, MspI, and EcoRI) in the Taiwanese (Wu et al 1993), the combined genotype frequencies of the Buryat differed significantly (P = 0.008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Combined genotypes or haplotypes for APOB polymorphisms consisting of some sites of the gene region have been described frequently in various ethnic populations (Renges et al 1992;De Benedictis et al 1993;Wu et al 1993;Hansen et al 1994;Hallman et al 1994;Anderson et al 1997;Hong et al 2001;Puri et al 2003). In comparison with the combined genotypes of four sites (AluI, XbaI, MspI, and EcoRI) in the Taiwanese (Wu et al 1993), the combined genotype frequencies of the Buryat differed significantly (P = 0.008).…”
Section: Discussionmentioning
confidence: 95%
“…Of the two most common combined genotypes (0000 and 1000), the frequency of 0000 was lower in the Buryat (56%) than in the Taiwanese (71%), and for 1000, no difference was recognized (28% vs. 21%). It has been shown that the frequency distribution of haplotypes at five sites (Ins/Del, AluI, XbaI, MspI, and EcoRI) in Koreans (Hong et al 2001) differs considerably from that of the Buryat. Despite the frequency of 67% of the haplotype code 00000 in the Buryat, the Koreans lacked it completely.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the distribution of different APOB haplotypes varies greatly in different populations. For example, the TT genotype (rare allele) frequency in the East Asian population (0.01-0.04) (Aburatani et al 1987;Hong et al 2001;Pan et al 1995;Wu et al 1994;Xu and Zhou 1998;Yan et al 2003;Ye et al 1995Ye et al , 1994Zang et al 2001;Zhang et al 2010Zhang et al , 2002 in our included studies was much lower than that in the Caucasian population (0.5) (Bohn et al 1993;Genest et al 1990;Hegele et al 1986), which may have caused the opposing results regarding its association with CAD/MI risk between the Caucasian and Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of the included studies are listed in Table (1a, 1b, 1c, 1d, in Supplementary document). A total of 47 eligible studies (Aburatani et al 1987;Al-Bustan et al 2009;Anghebem-Oliveira et al 2009;Beneš et al 2000a, b;Berkinbayev et al 2014;Bohn et al 1993Bohn et al , 1994Buraczynska et al 2000;Corbo et al 1997;De Lorenzo et al 1993;de Padua Mansur et al 2000;Duman et al 2005;Dunning et al 1993;Ferns and Galton 1986;Gallegos-Arreola et al 2012;Gardemann et al 1998;Genest et al 1990;Hegele et al 1986;Hong et al 2001;Hosking et al 1992;Huang et al 2012;Kallel et al 2008;Machado et al 2001;Marshall et al 1994;Mendis et al 1991;Miettinen et al 1994;Myant et al 1989;Nieminen et al 1992;Pan et al 1995;Paulweber et al 1990;Rebhi et al 2008;Saha et al 1992;Salazar et al 2000;Scartezini et al 2003;Stepanov et al 1998;Tybjaerg-Hansen et al 1991;Visvikis et al 1993;Wiklund et al 1989;Wu et al 1994;Xu and Zhou 1998;…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…17,18,45,46 The allelic variation of apo B gene polymorphisms may have some association with various ethnic groups. The EcoRI Rþ/Rþ genotype has been reported to occur most frequently among Koreans, 47 Japanese, 32 Caucasions, 33 and multiethnic Asian populations, 10 whereas the EcoRI RÀ/RÀ genotype has been shown to be the major genotype in Finns 34 and Caucasions generally. 48,49 In our study, the Rþ/Rþ genotype was found to be the highest in frequency when compared to Rþ/RÀ and RÀ/RÀ in both patients and controls.…”
Section: Discussionmentioning
confidence: 99%